Protection of Interest of Investment Funds Participants in the Context of Closet Indexing - Miziołek, Tomasz (Journal of Finance and Financial Law, 2016)
Closet indexing is a practice used by asset management companies consisting in relatively passive portfolio management by funds declaring an active approach to management, while charging relatively high management fees, inadequate to demonstrated commitment. As the results of research carried out by national supervisory authorities, independent analytic firms as well as European Securities and Markets Authority (ESMA) show, closet indexing is experienced – with varying intensity – by many European countries and exposes investors on significant losses.